8 Chemoenzymatic Dynamic Kinetic Asymmetric Transformation - Pàmies,O. (Dynamic Kinetic Resolution (DKR) and Dynamic Kinetic Asymmetric Transformations (DYKAT), 2023)
The combination of enzymes and metal complexes can be used to achieve the de-epimerization of diastereoisomeric mixtures. Thus, by means of this chemoenzymatic dynamic kinetic asymmetric transformation (DYKAT), a wide range of racemic diols and, to a lesser extent, amino alcohols and diamines, have been transformed into a single diastereoisomer in excellent yields, and diastereo- and enantioselectivities.
Keywords: Referencework; dynamic kinetic asymmetric transformation; DYKAT; enzymes; metal complexes; diols; amino alcohols; diamines; chirality